Đáp án:
Bài `6`:
`(x - 3)(x + 5) - (x- 2)(x + 2)`
`= x^2 + 5x - 3x - 15 - (x^2 - 2^2)`
`= x^2 + 5x - 3x - 15 - x^2 + 4`
`= (x^2 - x^2) + (5x - 3x) + (-15 + 4)`
`= 2x - 11`
* Áp dụng hằng đẳng thức: `A^2 - B^2 = (A + B)(A - B)`
Bài `7`
`(x - 1)^2 - 2(x - 3)(x - 1) + (x - 3)^2`
`= [(x - 1) - (x- 3)]^2`
`= (x - 1 - x + 3)^2`
`= 2^2`
`= 4`
`⇒` $\text{Biểu thức không phụ thuộc vào biến}$
* Áp dụng hằng đẳng thức: `(A - B)^2 = A^2 - 2AB + B^2`
Bài `9`:
Ta có: `4x^2 + 20x - 7`
`= 4x^4 + 20x + 25 - 25 - 7`
`= (2x)^2 + 2.2x.5 + 5^2 - 32`
`= (2x + 5)^2 - 32`
Vì: `(2x + 5)^2 ≥ 0`
`⇒ (2x + 5)^2 - 32 ≥ - 32`
Suy ra: Min `= - 32`, khi `(2x + 5)^2 = 0`
`⇔ 2x + 5 = 0`
`⇔ 2x = - 5`
`⇒ x = -5/2`
Vậy Min `= - 32`, khi `x = -5/2`